Analisis Korelasi Pearson Dalam Menentukan Hubungan Harga Dengan Volume Penjualan Wardah Matte Lip Cream Pada Platform E-Commerce Shopee - Ardhaneswari, Pande Putu Narisya; Suwitra, I Wayan Candra (Jurnal Ilmiah Sains Sosial, Kewirausahaan dan Kebudayaan, 2024)
This research aims to identify how much influence price has on Wardah Matte Lip Cream product volume on the online shopping site Shopee. The population of this research is all shops in the Jabodetabek area. The samples used in this research were 50 shops in the Jabodetabek area (Jakarta, Bogor, Depok, Tanggerang, Bekasi) that sell Wardah Matte Lip Cream. Proportional Random Sampling is the sampling method used, where data analysis is carried out using Parametric Analysis because this analysis must have a normal distribution. Statistical testing was conducted using the normality test and Pearson correlation. The outcome of the data studies indicate that price possesses negative effect on the volume of Wardah Matte Lip Cream products. This is proven through the Pearson correlation test that the sig (2-tailed) results show 0.002, which is below 0.05 which shows that there is a correlation between each test variable and the opposite (negative) bond characteristic, namely -0.422. The findings of this study demonstrate that, although there is a moderate correlation, cheaper prices are the reason why Wardah Matte Lip Cream products are purchased more often in cosmetics stores in the Jabodetabek area.